2014
DOI: 10.1111/add.12753
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effects between the 5‐hydroxy tryptamine transporter‐linked polymorphic region (5‐HTTLPR) genotype and family conflict on adolescent alcohol use and misuse

Abstract: Compared with non-carriers, adolescents carrying the 5-HTTLPR low-activity allele are more susceptible to the effects of family conflict on alcohol misuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…In a study done by Nilsson et al (2005), 5-HTT genotype and family relations interacted with one another and marginally predicted alcohol consumption in a group of 200 adolescents (p=0.05). Similar results were observed in a study by Kim et al (2015) among 5091 adolescents where a significant gene × environment interaction influenced alcohol misuse in these participants. This study showed that low-activity alleles of 5-HTTLPR polymorphisms (S and LG alleles), when compounded with family conflicts, resulted in significant increase in alcohol misuse.…”
Section: Discussionsupporting
confidence: 89%
“…In a study done by Nilsson et al (2005), 5-HTT genotype and family relations interacted with one another and marginally predicted alcohol consumption in a group of 200 adolescents (p=0.05). Similar results were observed in a study by Kim et al (2015) among 5091 adolescents where a significant gene × environment interaction influenced alcohol misuse in these participants. This study showed that low-activity alleles of 5-HTTLPR polymorphisms (S and LG alleles), when compounded with family conflicts, resulted in significant increase in alcohol misuse.…”
Section: Discussionsupporting
confidence: 89%
“…Data for this study were collected as part of the first assessment in a prospective, community-based study of 250 adolescents (29,30). Adolescents were recruited from both school and community venues.…”
Section: Methodsmentioning
confidence: 99%
“…45 In middle adolescence (mixed races), when they reported high levels of family conflict at 12, youth carrying low activity allele showed higher risk of drinking at age 15 than non-carriers. 25 Similarly, in middle and late adolescence (Swedish; race was not reported), when they reported poor family relations, youth carrying one long and one short allele were more likely to drink and get intoxicated cross-sectionally at ages 12 and 15 in two independent samples. 46 A study of Caucasian young adults also reported that, when exposed to higher levels of negative life events, college students carrying at least one short allele were more likely to engage in binge drinking (defined as 4 or more drinks for women and 5 or more drinks for men on one setting: 4þ/5þ) than non-carriers.…”
Section: -Hydroxy Tryptamine Transporter Linked Promoter Region (5-hmentioning
confidence: 98%
“…Twenty four out of the 42 identified studies were conducted in the United States, and the remaining studies were conducted in Germany (n ¼ 7), the Netherlands (n ¼ 5), Sweden (n ¼ 3), Australia (n ¼ 2), Estonia (n ¼ 1), and the United Kingdom (n ¼ 1). Among them, one study 25 used one sample collected in the United States and another in the United Kingdom.…”
Section: Sample Characteristicsmentioning
confidence: 99%